PERLINDUNGAN HUKUM TERHADAP KONSUMEN AKIBAT PEREDARAN KOSMETIKA ILEGAL HB WHITENING BERDASARKAN HUKUM PERLINDUNGAN KONSUMEN : - Tsuraya Amalia; Dian Purnamasari (Reformasi Hukum Trisakti, 2023)
Cosmetic products are currently increasingly demand, in the purchasing process there are many factors that make people buy using online buying and selling services. When buying online, sometimes buyers are less careful in buying products sold by business actors who ignore the terms of sale of cosmetics, so consumers are harmed. For example, HB Whitening lotion products that contain harmful ingredients but are still traded. The subject matter of this article is how is the legal protection of HB Whitening consumers that results in harm to consumers and find out how the efforts of the Food. The research method used is normative type, descriptive in nature, by sourcing secondary data which will be analyzed qualitatively and deductively drawn conclusions. Based on the results of the study, HB Whitening has provided insecurity for consumers because there is an element of harm in it, thus violating Article 4 of the GCPL and must be responsible for consumers based on Article 19 of the GCPL. BPOM has made preventive and persuasive efforts, but in tackling the circulation of HB Whitening products is still not in accordance with the applicable provisions.